Intersecting Disability and Poverty in the Global South: Barriers to the Localization of the UNCRPD - Shaun Grech; Jörg Weber; Sarah Rule (Social Inclusion, 2023)
The UN Convention on the Rights of Persons with Disabilities (UNCRPD) remains in place as the major disability rights instrument recognising that all persons with disabilities must enjoy human rights and freedoms as every other person. However, the CRPD does not automatically confer realization of these rights. In practice, its implementation is met by multiple hurdles, most pronounced at the local level in the Global South, where disability and poverty intersect. This article reports on findings from a study in five countries (Kenya, Philippines, Jamaica, Guatemala, and South Africa) looking at the extent to which the CRPD is being implemented locally in contexts of poverty, and the factors and processes impacting this localization. The findings highlight multiple barriers, becoming more pronounced in local rural areas. These include weak and fragmented organisations of persons with disabilities (OPDs), political and legal issues, and a siloed approach where disability is marginalised in mainstream areas, including development. These barriers are accentuated as intersectional dimensions are factored in, including indigeneity, age, gender, race, and ethnicity. Overall, each local context is left to its own devices, with urban stakeholders, unknowing of what life in poverty is like and how this reframes the CRPD in discourse and practice at the forefront. Our study concludes that there is a profound need for an informed, contextualized, intersectional, and geopolitical analysis where poverty is kept sharply in focus. This is essential to move beyond unrealistic assumptions about disability rights frameworks and to work towards truly localized and transformative efforts.